Trastuzumab combined chemotherapy for the treatment of HER2-positive advanced gastric cancer: A systematic review and meta-analysis of randomized controlled trial. Issue 34 (26th August 2022) - Xue, Chuan; Xu, Yong-Hong
Abstract : Background: This systematic review and meta-analysis aimed to assess the efficacy of trastuzumab combined with chemotherapy for the treatment in HER2-positive advanced gastric cancer (HER2-PAGC). Methods: This systematic review and meta-analysis was designed using randomized controlled trials that compared trastuzumab in combination with chemotherapy and chemotherapy alone. A comprehensive search was conducted in the following databases from their inception onwards: PubMed, EMBASE, Cochrane Library, WANGFANG, and CNKI. We also searched other literature sources to avoid missing relevant studies. Two reviewers independently performed all record selection, data collection, and methodological assessments. Any confusion was resolved by discussion or referral to a third reviewer. If there were ample data from eligible studies, we performed a fixed-effects meta-analysis. Whenever this was not possible, we conducted a narrative synthesis. Results: Meta-analysis results showed that trastuzumab in combination with chemotherapy achieved better outcomes on response rate (trastuzumab plus CFC vs CFC: odds ratio [OR] = 1.56, 95% confidence interval [CI] [1.17–2.09], I 2 = 0%, P < .003; trastuzumab plus OT vs OT: OR = 2.97, 95% CI [1.74–5.09], I 2 = 0%, P < .0001; and trastuzumab plus CC vs CC: OR = 2.62, 95% CI [1.84–3.73], I 2 = 0%, P < .0001), and disease control rate (trastuzumab plus CFC vs CFC: OR = 1.61, 95% CI [1.17–2.21], I 2 = 0%, P = .004; trastuzumab plus OT vs OT: OR = 4.29, 95% CI [2.33–7.90], I 2 = 0%, P < .0001; and trastuzumab plus CC vs CC: OR = 2.99, 95% CI [1.99–4.48], I 2 = 0%, P < .0001). However, there were no significant differences in the adverse events. Conclusions: The results of this study revealed that the efficacy of trastuzumab combined with chemotherapy was superior to that of chemotherapy alone for the treatment of HER2-PAGC. The 2 modalities showed similar safety profiles.